Retrieval of Leaf Area Index using IRS-P6, LISS-III data and validation of MODIS LAI product (MOD15 V5) over trans Gangetic Plains of India - TRIPATHI, RAHUL; SAHOO, R N; GUPTA, V K; SEHGAL, V K; SAHOO, P M (The Indian Journal of Agricultural Sciences, 2026)
The mapping of leaf area index (LAI) in large geographic area may be impossible when we rely on theÂ  field measurement. To solve this problem, there have been continuing efforts to develop methodologies to estimate LAI using remote sensor data. Different methods to estimate LAI from reflectance data have been developed and can be grouped into two approaches such as (1) statistical approach and (2) physical process based approach. In this study, statistical approach has been used to retrieve the LAI of a part of north western part of the country using LISS-III, IRS P6 sensor. Using physical process based approach (i e radiative transfer model) MODIS on-board Earth Observing System (EOS) Terra/Aqua platforms, now provide LAI as a standard product (MOD15) to the scientific community at 1 km resolution, every eight days. The validation of LAI products by comparison to reference field LAI values is necessary and has been carried out for many sites over USA, Africa but very few results are available over India, hence MOD 15 LAI products have been validated using the derived LAI of LISS-III which was aggregated to 1 km resolution. Results revealed positive correlation (R2 = 0.62) between MODIS LAI product and aggregated LISS-III LAI but MODIS LAI values were found to be underestimated compared to the measured values. The overall RMSE of MODIS LAI is higher (ie 2.74) compared to LISS-III LAI (0.65).